Exploring the impact of massification of higher education on the labour force participation and empowerment of Malaysian women - Elhadary, Yasin; Ahmed, Abdalla (Asian Development Policy Review, 2024)
This paper aims to investigate the mismatch between the massification of higher education and the participation of women in the labour force in Malaysia. The objective is to statistically uncover the effect of educational attainment on the female labour force participation rate. The paper analyzed the data collected from various sources, like the World Bank, the World Economic Forum, and the Department of Statistics Malaysia. The paper employed various hypotheses tests, including the independent samples T-test, Mann-Whitney test, and Kruskal-Wallis test, to assess the relationship and determine whether to accept or reject the study hypotheses. The finding showed that females substantially outnumbered males among higher education’s graduates. Despite this improvement, women remain underrepresented in the labour force compared to the rate of their education attainment as well as that of men. The paper statistically rejects the notion that there is a positive linear connection between educating women and labour force participation. It is not all about educating women; decision-makers have to search for other factors that hinder women from fully participating in the labour force, particularly in the world of Muslim nations. The paper enriches the literature on gender parity and contributes to the ongoing debate about the effect of education on female labour force participation.